Taking products of scientific research from the lab to the public a communication plan to build the image of sago noodles as a consumer product - Gamalong, Alethea Louise D.
Because of the dynamics of science communication has been limited to the communication of tangible products of scientific research as products of science; this study explored the application of marketing, particularly public relations, to take products of scientific research to the public as consumer products. Using the sago noodles as a case in point, this thesis made use of science communication to communicate products of scientific research to the intermediary influential (private sector, government and media) and marketing principles and techniques to communicate to the general public. Using the product differentiation approach, the following are the identified bases of differentiation of the sago noodles: healthy, naturally nutritious and more affordable than regular and enriched wheat-based noodles. The STP (Segmentation-Targeting- Positioning) process model was also used. For the case of the sago noodles, the target market was the Davao City population, primarily the low-income consumers as most vulnerable to misinformation or lack of health information, malnutrition and food unavailability. The position that was identified was basically that of a noodle product that is healthy, naturally nutritious and more affordable than regular and enriched wheat-based noodle. The consumer-decision making process and the adult learning cycle were applied in this research to determine how to reach the target public. All of the above-mentioned principles and techniques were incorporated in the ROPE process of the communication plan and were used as bases for the strategies identified. As a result, a sample communication plan using the sago noodles has been produced.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication